Question and Answers Forum

All Questions      Topic List

Number Theory Questions

Previous in All Question      Next in All Question      

Previous in Number Theory      Next in Number Theory      

Question Number 203146 by Rasheed.Sindhi last updated on 11/Jan/24

Determine ab^(−)  (a>b) such that( ab^(−) +ba^(−) )   and (ab^(−) −ba^(−) ) are both perfect squares.

$$\mathcal{D}{etermine}\:\overline {{ab}}\:\left({a}>{b}\right)\:{such}\:{that}\left(\:\overline {{ab}}+\overline {{ba}}\right)\: \\ $$$${and}\:\left(\overline {{ab}}−\overline {{ba}}\right)\:{are}\:{both}\:{perfect}\:{squares}. \\ $$

Answered by Frix last updated on 11/Jan/24

10a+b+10b+a=p^2  ⇔ 11(a+b)=p^2   10a+b−10b−a=q^2  ⇔ 9(a−b)=q^2   ⇒  a+b=11∧(a−b=1∨a−b=4)  b=11−a ⇒ a−b=2a−11  2a−11=1 ⇒ a=6∧b=5 ★  2a−11=4 ⇒ a∉N

$$\mathrm{10}{a}+{b}+\mathrm{10}{b}+{a}={p}^{\mathrm{2}} \:\Leftrightarrow\:\mathrm{11}\left({a}+{b}\right)={p}^{\mathrm{2}} \\ $$$$\mathrm{10}{a}+{b}−\mathrm{10}{b}−{a}={q}^{\mathrm{2}} \:\Leftrightarrow\:\mathrm{9}\left({a}−{b}\right)={q}^{\mathrm{2}} \\ $$$$\Rightarrow \\ $$$${a}+{b}=\mathrm{11}\wedge\left({a}−{b}=\mathrm{1}\vee{a}−{b}=\mathrm{4}\right) \\ $$$${b}=\mathrm{11}−{a}\:\Rightarrow\:{a}−{b}=\mathrm{2}{a}−\mathrm{11} \\ $$$$\mathrm{2}{a}−\mathrm{11}=\mathrm{1}\:\Rightarrow\:{a}=\mathrm{6}\wedge{b}=\mathrm{5}\:\bigstar \\ $$$$\mathrm{2}{a}−\mathrm{11}=\mathrm{4}\:\Rightarrow\:{a}\notin\mathbb{N} \\ $$

Commented by Rasheed.Sindhi last updated on 11/Jan/24

Thanks sir!

$$\mathbb{T}\boldsymbol{\mathrm{han}}\Bbbk\boldsymbol{\mathrm{s}}\:\boldsymbol{\mathrm{sir}}! \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com